IMPLEMENTATION OF SOCIOLOGY LEARNING WITH PBL MODEL IN THE INDEPENDENT CURRICULUM AT SMA NEGERI 1 CISARUA WEST BANDUNG REGENCY - Sri Mulyanti; Yadi Ruyadi; Wilodati Wilodati (Universitas Negeri Medan, 2024)
Sociology subjects are expected to instill the ability to analyze phenomena and solve social problems in students later, but in reality it is considered an unimportant subject and less desirable by students. This is due to the use of learning methods and models that are not varied by teachers in teaching so that student learning interest becomes minimal and ultimately has an impact on students' lack of understanding of sociological material. Problem Based Learning (PBL) is one of the recommended learning models in the independent curriculum, because PBL provides opportunities for students to apply their concepts to real situations. So it requires students to think critically in solving every problem. This study aims to see how the implementation of sociology learning with the PBL model in the independent curriculum at SMA Negeri 1 Cisarua. This research uses a qualitative approach with a case study method. Informants are selected by purposive sampling techniques and the key informants are teachers of sociology subjects in class XI, while supporting informants are vice principals for curriculum and grade XI students who take sociology elective subjects. Data analysis is carried out by data reduction, data presentation, and conclusions. Then to test the validity of the data, researchers use triangulation of data collection techniques and triangulation of data sources. From the results of the study, it was found that the implementation of sociology learning with the PBL model in the independent curriculum at SMA Negeri 1 Cisarua was the same as when the previous curriculum still followed the syntax of the PBL model that had been conceptually determined, the difference was only in the existence of learning patterns in the independent curriculum such as differentiated learning, essential materials and the existence of the P5 program.